The Church College Trusts 1989 - Gay, JD (West Sussex Institute of Higher Education, 1989)
This chapter forms part of a book celebrating 150 years of the church colleges in higher education. At the end of the 1970s, the number of Anglican church colleges of education were reduced from 27 down to 13. Of the remaining 14, two were merged with other Anglican colleges, a further 3 were merged with their local polytechnics, 5 were taken over by their local universities and 4 were closed outright. Eleven of these former colleges became educational trusts with the residual assets of their old colleges vested in them. The processes whereby they became trusts are described and their new purposes outlined. At an early stage they established a mutual help organisation, the Association of Church College Trusts which quickly became a body through which trusts could also sponsor work collaboratively. There is a short section describing each of the trusts – The All Saints Educational Trust; The Culham Educational foundation; The Hockerill Educational Foundation; The Keswick Hall Charity; the St Gabriel’s Trust; The St Hild and St Bede Trust; The St Luke’s College Foundation; The St Mary’s College Trust; The Foundation of St Matthias; The Sarum St Michael Charity and the St Peter’s Saltley Trust. Looking back over their first ten years of life, certain features emerge. Each trust is autonomous and has carefully safeguarded its independence. Considering that they all grew out of colleges of higher education, there has been a substantial movement away from the central concerns of the surviving colleges including teacher education towards church issues and religious education. Relatively little of their resource has been channelled towards the surviving colleges perhaps reflecting a feeling that survival was achieved at the expense of those which were closed. Twenty-seven years later the church college trusts were further reviewed as part of an article by John Gay titled The training of RE teachers and the role of the Church college trusts in supporting them, published in Gates B (editor) Religion and Nationhood, Mohr Siebeck, Tubingen Germany, 2016.